Suitability of Different Forest Species for Social Forestry Programme under Different Soil Conditions. Part III-coastal Soil - Nath, S.; Das, P. K.; Gangopadhyay, S. K.; Banerjee, S. K.; Singh, Balvinder (Indian Forester, 1991)
The growth of different forest species planted in road-sides and canal-banks has been correlated with the soil attributes in coastal zone of Midnapore district, West Bengal. Some of the sites having better nutritional status accelerates the growth of some selected species. On the basis of the results some species have been recommended for Social Forestry Programme under the said soil condition in a given climatic zone.